Where should "Humans" be in "One Health"? Lessons from COVID-19 for One Health - Zhaohui Su; Dean McDonnell; Ali Cheshmehzangi; Barry L. Bentley; Sabina Šegalo; Claudimar Pereira da Veiga; Yu-Tao Xiang (BMC, 2024)
Abstract The culling of animals that are infected, or suspected to be infected, with COVID-19 has fuelled outcry. What might have contributed to the ongoing debates and discussions about animal rights protection amid global health crises is the lack of a unified understanding and internationally agreed-upon definition of "One Health". The term One Health is often utilised to describe the imperative to protect the health of humans, animals, and plants, along with the overarching ecosystem in an increasingly connected and globalized world. However, to date, there is a dearth of research on how to balance public health decisions that could impact all key stakeholders under the umbrella of One Health, particularly in contexts where human suffering has been immense. To shed light on the issue, this paper discusses whether One Health means "human-centred connected health" in a largely human-dominated planet, particularly amid crises like COVID-19. The insights of this study could help policymakers make more informed decisions that could effectively and efficiently protect human health while balancing the health and well-being of the rest of the inhabitants of our shared planet Earth.